Endophytic actinomycetes from mangrove plant \(Avicennia marina\) in Quang Ninh province, Vietnam: distribution, cytotoxicity, and antioxidant activities - Quach, Ngoc Tung; Bui, Thi Lien; Vu, Thi Hanh Nguyen; Nguyen, Thi Thu An; Chu, Hoang Ha; Phi, Quyet Tien (Academia Journal of Biology, 2022)
Mangrove endophytes have recently gained considerable attention due to their diversity and abundance of novel bioactive secondary metabolites. Despite the fact that Streptomyces species are producers of more than 75% of commercialized antibiotics, Streptomyces associated with the extremely widespread mangrove plant Avicennia marina remain poorly characterized. In this study, nine actinomycetes were isolated from A. marina growing in a mangrove forest, as yet unexplored, of Quang Ninh province, Vietnam. Phylogenetic analysis of actinomycetes-specific 16S rRNA sequences indicated that they were subjected to five Streptomyces species including Streptomyces cacaoi, Streptomyces californicus, Streptomyces enissocaesillis, Streptomyces coelicoflavus, and Streptomyces variabilis, which have not been previously reported in mangrove plants. Among them, S. cacaoi AM1 showed strong inhibition effects against six tested pathogenic bacteria with inhibitory zones ranging from 7.5−22.3 mm. Using standard 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, 100 µg/mL ethyl acetate extract of AM1 showed potent cytotoxicity against breast cancer MCF-7 and lung cancer A549 cell lines with cell viability of 16.5 ± 1.28% and 17.69 ± 2.3%, respectively. As for antioxidant activities, AM1 extract exhibited strong antioxidant activities against 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical (92.4 ± 0.004%) and superoxide anion radical (42.4 ± 0.019%), which were positively correlated to high polyphenol (84.3 ± 3.4 µg GAE/g FW) and flavonoid (34.9 ± 4.8 µg QE/g FW) contents. These findings indicated that S. cacaoi AM1 could be a promising reservoir of antibacterial, anticancer, and antioxidant agents. This is the first report of mangrove endophytic Streptomyces derived from A. marina.